"The Economics of Reform in the Middle Ages" - Jasper, Kathryn L. 19XX- (History compass, 2012)
Scholarship has long recognized the primary economic mission of eleventh-century Church reform as the restitution and protection of ecclesiastical property. Most monographs on the subject of reform regard the economic changes of the period as fundamental to wider negotiations of power. While the study of land tenure offers one context in which to examine how customary authority and canon law intersect, more recent work reveals a much more complex landscape of economic concerns. In particular, some excellent studies published in the last two decades consider the relationship between reform polemic and its manifestation on the ground. The interpretive shift towards a focus on local reform movements and the move towards studying the economic aspects of reform should often go hand in hand. In this way, we may arrive at a more holistic understanding of the economic issues raised during the most intense period of reform, from 1046 (Synod of Sutri) to 1122 (Concordat of Worms).